Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2020)
A dataset containing 1496623211 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false", "OccurrenceStatus is Present" ] } The dataset includes 1496623211 records from 25917 constituent datasets: 19 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 9 records from A review of the Indian species formerly assigned to the genus Storena Walckenaer, 1805 (Araneae: Zodariidae) with the description of a new genus. 32 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 6652 records from Inventory of plant species through Benin (West Africa). 505 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 550 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 4109 records from South Caribbean Diversity. 1127 records from marine sediment metagenome Metagenome. 499 records from Range table from benthic foraminifers in ODP Hole 146-889A. 2 records from A new species of Aspidura Wagler, 1830 (Squamata: Colubridae: Natricinae) from Sri Pada sanctuary (Peak Wilderness), Sri Lanka. 873 records from Programme ACT : Répartition Grive musicienne 2006 - 2010 Coordonnées GPS Lambert 93. 1968 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 371 records from Bannwald Burghauser Forst. 19 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 18 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 948 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 290 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 54 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 1741 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 20 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 13 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 107 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 2127 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 10 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 276 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 20520 records from University of Guam Insect Collection. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 756 records from Benthic foraminifera and algae abundance of Hole 81-552A. 1569 records from Pollen record of sediment core Bokanjacko Blato 1. 391 records from Planktic foraminifera abundance of Hole 32-310. 19 records from Dinoflagellate abundance of Hole 81-554. 3 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 82 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 102 records from Nannofossil abundance of Hole 24-232. 158 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 125 records from Total foraminifera counts of multinet M21/2_MSN650. 7283 records from Colecção Entomológica IIA. 2 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 16763 records from MZFC/Coleccion de Aves. 214 records from Total foraminifera counts of multinet M21/1_MSN608. 18190 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 5855 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 4038 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 7 records from Two new species of the bamboo-feeding planthopper genus Neobelocera Ding & Yang, 1986 from China (Hemiptera, Fulgoroidea, Delphacidae). 1297 records from Recensement et distribution Mammifères marins Guadeloupe Antilles françaises (AET). 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 272 records from Inventaire malacologique des murs restaurés en pierre sèche en lien avec l'association "une pierre sur l'autre". 78 records from Banco de Semillas de Boyacá. 1063 records from DMNS Egg Collection (Arctos). 2225 records from Données naturalistes d'Anaïs MAS. 1 records from New records of family Hormathiidae (Cnidaria: Actiniaria) from Brazilian coast with description of Paraphelliactis labiata n. sp.. 862 records from Palynological analysis of sediment core GeoB9508-5. 8 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 65 records from Données du/de la naturaliste Thibault Marie Thérèse provenant de la base de donnée du SINP Île-de-France CETTIA. 6 records from Abundance of benthos infauna at station GIK23065-1. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 27254 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 1 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 283 records from Flux data of NU2_trap (Table A1). 4 records from Planktic foraminifera abundance of Hole 17-166. 231 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 2842040 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 228 records from Bishop's University Insect Collection (BUIC). 5 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 18 records from ALTERECO_2017_12_18. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 361 records from An updated checklist of aquatic plants of Myanmar and Thailand. 5346 records from Sediment metagenome. 1702 records from BioGIS - Bryophytes - HUJ collections. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_6-CTD67. 15255 records from Anymals+plants - Citizen Science Data. 957 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 5156 records from Submarine Ligurian Canyons Water Prokaryotic and Protist Communities. 1571 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 849 records from CNAN/Scorpiones. 346 records from Universidad del Valle de Guatemala - Colección de Artrópodos. 1 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 2208 records from marine sediment metagenome Raw sequence reads. 13 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 400 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 6 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 776 records from Programme ACT : Répartition Pie bavarde 2010 - 2014 Coordonnées GPS Lambert 93. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 3093 records from EDP Baixo Sabor: Land Birds - Construction and Reservoir Filling Phases: stream weirs in the Sabor tributaries [2010-2014]. 424 records from Collection de C.C.H. Jongkind aux Monts Nimba. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 101 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 2 records from A new species of Trismegistomya Reinhard (Diptera: Tachinidae) from Area de Conservacion Guanacaste in northwestern Costa Rica. 44 records from Mamíferos pequeños en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 817 records from Programme ACT : Répartition Tourterelle turque 1997 - 2001 Coordonnées GPS Lambert 93. 2193 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 8 records from A review of the ant genus Metapone Forel from Madagascar.. 9 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 243 records from Thistles species and abundance. 115 records from On the absence of the Green-tailed Trainbearer Lesbia nuna (Trochilidae) from Venezuela: an analysis based on environmental niche modelling. 10 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 4511 records from SPC PROCFish/C Invertebrates Observations Solomon Islands 2006. 29559 records from Occurrences de vecteurs de maladies recensées à l'Hôpital de Mènontin. 2111 records from Flora vascular acuática de la cuenca del Río Tamesí. 5664 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 66 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 120 records from BIRDRACE The early birds. 1933 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 5 records from Two new nematode species of the genus Tobrilus Andrássy, 1959 (Nematoda, Triplonchida) from Lake Baikal, Russia. 92 records from Protozoa Abundance_Microbial Parameters. 17 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 1096 records from Données naturalistes de Stéphane ORIO. 702 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 155912 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 45 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 59788 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 32 records from Antarctic Pycnogonids II. 2560 records from Upper Silesian Museum, Bird Observations. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 847 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 135 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 127 records from SEWBReC Springtails and allies (South East Wales). 1 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 102 records from Benthic foraminifera abundance in ODP Leg 155 holes. 62 records from Polychaeta and Oligochaeta of the Auckland and Campbell Islands, New Zealand, 1941-1945. 158333 records from The Himalayan Uplands Plant database (HUP Version 1). 131 records from Artenvielfalt auf dem Schulgelände. 419 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 11 records from (Table 2) Population density and zoobenthos biomass in bottom communities of the Novosibirsk Polynya in September 2008. 237 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 69 records from BIRDRACE Pfeifenten. 5335 records from Marine metagenome ICM_JRV. 146 records from Données de la naturaliste Laurence Beauchamp. 52 records from Collections ichtyologiques et herpétologiques (BOUM). 78 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 18 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 686 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 99 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 6192 records from NE Scotland fish records 1800-2010. 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 57919 records from Fichier communal des ongulés. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 25 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 9176 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 115 records from Living Cirripedia. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 510 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 325 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 138 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 27 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 1189 records from UWIZM Molluscs. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 4083 records from MCP-Aves - Coleção de Aves. 135 records from Nannofossil abundance of Hole 36-329. 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 147 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 100 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 61 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 14 records from Nemertini - SMF. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 371 records from orthopteracollections-nhmj-ioj. 778 records from Bird specimens of Saitama Museum of Natural History. 1 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 56 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 10788 records from Collections of Bioclass, school #179, Moscow. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 988 records from flower availability 2008 Alb-korrigiert. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 4 records from Dinoflagellate abundance of Hole 14-144. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 34052 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 277417 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 34 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 2804 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 1 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 5 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 477 records from Planktic foraminifera distribution of sediment core SU81-07. 231 records from Range table from benthic foraminifers in ODP Hole 161-974B. 926 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 7 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 139 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 1156 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 13 records from Benthic foraminifera abundance of Hole 96-620. 86616 records from Marine Offshore Seabed Survey data held by JNCC. 99 records from Nanoplankton abundance at station GeoB2006-4. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 319 records from Données naturalistes de Monsieur LEFEBVRE François. 1543 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 18 records from Naturtag. 16071 records from Herbier Louis-Marie (QFA) - Collection de lichens. 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 131219 records from Herbarium of Taiwan Forestry Research Institute. 67 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 23 records from Ackerrain Plönhagen. 242 records from Malawi-Histeridae-Biodiversity-Data. 1004 records from Données odonates. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 1286 records from Planktic foraminifera abundance of Hole 7-64. 11 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 25 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 1089 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 420 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 1044940 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 413272 records from DATAVES. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 7 records from Planktic foraminifera abundance of Hole 53-418B. 14 records from Berea College, Ralph L. Thompson Herbarium. 409 records from Distribution of nanoplankton at trap WR2. 642 records from Análisis de la biodiversidad y servicios ecosistémicos para su aplicación en la toma de decisiones en el departamento de Boyacá/Boyacá Bio-Flora El Consuelo. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 17 records from Marine metagenome ICM_AGW. 78 records from Données de la naturaliste Anna Even. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 609 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 81 records from Kystfuruskoger i Tysnes og Fusa. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 29 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 87 records from Diatom abundance of Hole 95-613. 8 records from Die Bachspezies 2008/2009. 2364 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 73 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 68 records from Streuobstwiese. 23 records from Abundance of benthos infauna at station GIK23042-2. 197 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 659 records from Benthic foraminifera counts of sediment core GIK23352-3. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 247 records from Flora vascular y no vascular: expedición Cuenca Media del río Chicamocha - Proyecto Boyacá BIO UPTC. 47 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 2779561 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1009 records from Programme ACT : Répartition Merle noir 2012 - 2016 Coordonnées GPS Lambert 93. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 4616 records from Inventaire de la flore du Grand Poitiers 2009. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1461 records from M. Gollop Collection. 1 records from Données naturalistes d'Olivier DELZONS. 95 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 174 records from BIRDRACE Bon(n)apartemöwen. 10 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 6357 records from Distribution of foraminifera of sediment core GIK23258-2. 2497 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 2534 records from Elaboration de table de tarif de cubage multispécifique (I). 521 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 38 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 16 records from Insect Collections of Okomu National Park- Nigeria. 412 records from Heinersdorfer Sumpfwiese. 133642 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 279535 records from ARABEL - Arachnologia Belgica. 8 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 48 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 348 records from Antarctic pycnogonids. 60949 records from MLZ Bird Collection (Arctos). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 2592 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 380 records from UWYMV Herpetology Collection (Arctos). 2314 records from Midden-Limburg Fish Ponds Survey. 62595 records from Herbarium Senckenbergianum (FR) - Fungi. 1994 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 160 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 5 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 895 records from Geometridae de France métropolitaine. 18 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 174 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 1 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 1836 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 10354 records from Inventaire de la flore de Charente-Maritime 2018. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 2012 records from Pollen profile RAC20, Lake Racou, France. 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 10283 records from Inventario de Hymenóptera; parasítica en México. 374 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 8561 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1785 records from 3Soil16S. 715 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 9 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 30 records from Nannofossil abundance of Hole 24-233A. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 24 records from Dinoflagellate abundance of Hole 28-274. 50 records from Occurrence of mammalia relicts at site Biedermann. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 23136 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 27672 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 516 records from Planktic foraminifera counts of sediment core A15-558. 276 records from Birds Specimens of Akita Prefectural Museum. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 100 records from Données naturalistes de LE GLOANEC Vincent. 117837 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-71, 1974-5. 185 records from Size of planktic foraminifera at CTD station PS55/051. 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 792 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 7122 records from Whale catches in the Southern Ocean. 75 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 91 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 13868 records from Données faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 522 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 218 records from Land and freshwater molluscs of Northern Spain. 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3775 records from Données naturalistes de Charlotte PICARD. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 4 records from Ostracoda abundance of Hole 44-390. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 131 records from Manejo campesino sustentable del maguey papalote del Chilapan. Fase II. 28082 records from University of California Santa Barbara Invertebrate Zoology Collection. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 5460 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 85921 records from ALCB - Herbário Alexandre Leal Costa. 114 records from BIRDRACE LiLaLau. 80316 records from Fish specimens of Kagoshima University Museum. 3825 records from UTEP Invertebrates (Arctos). 163 records from Relative abundance of coccosphere-units at site GIK23414. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 3564 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 91 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 823 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 884 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 15 records from Nannofossil abundance of Hole 10-93. 122 records from Base de datos de las especies maderables del género Dalbergia en México, registros del Herbario Nacional de México (MEXU). 1422 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 275 records from Planktic foraminifera counts of sediment core V14-77. 13 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 38 records from Ours 2006 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 14 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 50 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 2508 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 251794 records from Phase 2 Lowland Grassland Survey of Wales. 267172 records from hymenoptera. 60 records from Amphibian and Reptilian (KIEE-AR). 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 40 records from Planktic foraminifera abundance of Hole 14-137. 2444 records from UWYMV Bird Collection (Arctos). 751 records from Données naturalistes de Monsieur JOURDE Rémi. 873 records from Programme ACT : Répartition Geai des chênes 2008 - 2012 Coordonnées GPS Lambert 93. 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 42 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 1146493 records from PlutoF platform observations. 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 130 records from Total foraminifera counts of multinet M21/6_MSN784. 48 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 132 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 38 records from Nannofossil abundance of Hole 10-89. 31 records from Bulletin d'informations de l'Association française de Lichénologie. 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 91 records from Nannofossil abundance of Hole 30-285A. 56 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 23646 records from WTSWW Data: All Taxa (West Wales). 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 11 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 69 records from Unter hellen Zinnen und finsteren Grotten. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 1003 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 134 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 6433 records from Modernisation des ZNIEFF du PnrL. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 20 records from Occurrence of mammalia relicts at site Niederlehme. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 38 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 1264 records from Grand Voyeux - Suivis scientifiques. 86 records from UWIZM Cnidarians. 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 80 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 174667 records from Tasmanian Museum and Art Gallery provider for OZCAM. 14341 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 938 records from TTRS Mammals. 6 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 6 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 4575 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 2 records from Benthic foraminifera abundance of Hole 42-376. 45 records from Brown bear monitoring data from Deosai National Park. 1232 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling at Pathogen Plots]). 669 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 93665 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 1 records from Occurrence of mammalia relicts at site High Furlong. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 36 records from University of Sindh Jamshoro Herbarium. 602 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 420 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 29 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 134 records from Faunal assemblage of sediment core TR149-32. 787 records from Programme ACT : Répartition Pie bavarde 2009 - 2013 Coordonnées GPS Lambert 93. 62 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 78 records from Planktic foraminifera counts at CTD station PS55/079-1. 111 records from Birdrace-Uhulogen-Lippe. 15 records from Feral Pigs - Sightings and Cull records - 2018-2019. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 7010 records from La familia Asclepiadaceae en México. 3 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 83 records from Birdrace-Die_Vogelscheuchen-Herford. 373 records from Otter survey of Ireland 2004 & 2005. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 133152 records from Suivi Temporel des Rhopalocères de France (STERF). 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 15 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 177 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 38 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 561 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 61 records from Alien Species in Poland - Plants. 323 records from Données de VINCENT Alexis (SAPROX). 56 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 14 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 135 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 361 records from Nannofossil abundance of Hole 66-490. 130 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 449 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 238 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 820 records from Nannofossil abundance of Hole 82-558A. 446 records from Programme ACT : Répartition Etourneau sansonnet 2006 - 2010 Coordonnées GPS Lambert 93. 3327 records from BioGIS - Mammals - SPNI. 511 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 13 records from Diatom abundance of Hole 60-460. 18 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 18 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 194 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 3406 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 130 records from Total foraminifera counts from multinet SO119_MSN1285. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 5883 records from MfN - Fossil vertebrates IV. 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 36835 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 1607 records from MEXU/Flora de Oaxaca. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 6445 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 207 records from Nannofossil abundance of Hole 66-488. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 97 records from Amphibiens filet/Marbotte-Ronval 2013. 3319 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 53 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 76 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 123 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 18 records from Anfibios presentes en el Cerro Jánano. 120 records from Données espèces - Expertise IPE 79. 1709628 records from NBIS Records to December 2016. 27 records from Planktic foraminifera abundance of Hole 51-417B. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 2826 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 931 records from South American Antarctic Marine Biodiversity Literature. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 81 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 5 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 51 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 911 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 1930 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 17 records from Thirteen new records of ferns from Brazil. 713 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 384 records from Marine metagenome ICM_AWP. 3579 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 4 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 121 records from Foraminifera abundance of sediment core IN68-28. 26 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 4780 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 98 records from Données opportunistes sur les odonates. 14980 records from Données Entomologiques A. HORELLOU 1988-2018. 285 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 540 records from Foraminifera abundance of Hole 74-526A. 48 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 237 records from Planktic foraminifera abundance of Hole 21-207. 24 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 15 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 11321 records from WOLL AVH data. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 19 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 84 records from Ostracoda abundance of Hole 48-403. 34 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 2714 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 94 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 2497 records from Données des collections d'algues du MNHN. 76 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 2266 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 6 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 10766 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 7 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 3500 records from Pelagic sediment metagenome of Gulf of Kutch. 20 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 68910 records from Données de l'Observatoire de la Faune de Bourgogne. 1184 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 255 records from Programme ACT : Répartition Perdrix rouge 2009 - 2013 Coordonnées GPS Lambert 93. 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 4389 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 5 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 539 records from Phenological Center - Birds (Murmansk). 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 100 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 187 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 320 records from Echinoderms from the Seaflower Biosphere Reserve. 100 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 198 records from Programme ACT : Répartition Alouette lulu 1996 - 2000 Coordonnées GPS Lambert 93. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 117 records from Nannofossil abundance of Hole 49-408. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 17 records from Analyses of the recent components of sediment core PS1011-1. 24 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 29 records from MVZ Herp Observations (Arctos). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 6 records from Foraminifera abundance of Hole 58-442. 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 13 records from Coleção de Coleoptera da Universidade de Brasília. 396 records from (Table 2) Species composition of algae and cyanobacteria encountered in plankton of the Large Aral Sea on June 2-8, 2008. 98 records from Warnowtal (Rostock). 26 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 2 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 2747 records from Compost microbe establishment and growth in agricultural soils. 202114 records from National Benthic Inventory. 16 records from Phenological Center - Fishes (Murmansk). 358 records from Comunidad fitoplanctónica presente en la Bahía de Buenaventura 2018. 63 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 111 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 351778 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 886 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 178 records from Benthic foraminifera and algae abundance of Hole 81-554. 243917 records from Carnet B Lorraine. 27 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 346977 records from Seasearch Marine Surveys in England. 35 records from Planktic foraminifera abundance of Hole 84-566C. 9 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 2963 records from Collection Trichoptera - SMF. 16 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 3740 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 1798 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 751 records from Planktic foraminifera abundance of Hole 27-262. 121506 records from Arizona State University Hasbrouck Insect Collection. 35 records from Planktic foraminifera abundance of Hole 27-260. 77 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 3361 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 35 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 1480 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 87901 records from MDFRC macroinvertebrate survey. 128 records from Inventaire des reptiles 2014. 589 records from Programme ACT : Répartition Pie bavarde 2005 - 2009 Coordonnées GPS Lambert 93. 53 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 6 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 1168 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 105 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 9373 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 20440 records from Inventaire de la flore de Charente-Maritime 2017. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 4853 records from Inventaire des espèces végétales du sous bois des plantations de Teck de la forêt naturelle de la Lama. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 411 records from SuLaMa reptile survey I 2012. 61 records from Shrews of Poland. 9 records from Nannofossil abundance of Hole 2-11. 2 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 238 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0012A. 2371 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 186 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 15 records from Nannofossil abundance of Hole 6-48B. 181700 records from Marine benthic dataset (version 1) commissioned by UKOOA. 5229 records from European Moth Nights. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 172 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 6775 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 1462 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 1036 records from BUND - Dassower See (Lübeck/Dassow). 59995 records from Données naturalistes de Monsieur François FOURNIER. 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 54016 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 4 records from Sächsische Schweiz (Wehlener Gebiet). 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 29 records from Ours 2004 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 7653 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 35 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 5 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 255 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 10295 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 16506 records from Database for alien invasive plants occurrences in Germany. 66 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 1335 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 466 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 364 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 3673 records from Spider (NSMK-SP). 4124 records from OUPR - Herbário "Professor José Badini". 10 records from Nannofossil abundance of Hole 58-442B. 17 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 334 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 12399 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 92 records from Nottekanal, Klasse 7 - 10. 574 records from Percentages of planktonic foraminifera species in sediment core V30-40. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 4733 records from Inventaire des Mollusques Sphaeriidae de France. 742 records from Programme ACT : Répartition Alouette des champs 2000 - 2004 Coordonnées GPS Lambert 93. 16885 records from données aranéologiques de CORNIC Jean-François. 54 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 2929 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 3919 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 1 records from Filogeografia mitocondrial y nuclear de la Tangara rosada Rhodinocichla rosea (Lesson, 1832): el efecto del aislamiento geográfico y el nicho ecológico en los procesos de divergencia evolutiva.. 50 records from Flora und Fauna im Brexbachtal. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14626 records from Ontario Breeding Bird Atlas 1981-1985. 6926 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 3399 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 391 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 273 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 45367 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 133 records from Pollen profile II/B at Krumbach, Germany. 12705 records from Weevil and Bark Beetle Recording Scheme - data verified via iRecord. 51 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 1067 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 38 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 2 records from Nannofossil abundance of Hole 4-26A. 92 records from Planktic foraminifera abundance of Hole 22-212. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 173 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 39 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 86 records from Données naturalistes de Pierre-Alexis RAULT. 60 records from Wichita State University Collection. 4 records from A new species of the fangblenny Adelotremus from Indonesia, with supplemental description of A. leptus (Teleostei: Blenniidae: Nemophini). 8158 records from Dark ocean microbial diversity. 10 records from A taxonomic revision of the Strumigenys nitens and simulans groups (Hymenoptera: Formicidae), two Caribbean radiations of leaf litter ants. 327 records from pbzt_insect_biodiversity. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 253 records from NZCS Upper Tapanahony Expedition 1991. 307 records from Chronicle of Nature - Phenology of Amphibia of Darwin Nature Biosphere Reserve. 22 records from Tanzanian Vertebrate Collection. 4 records from A new species of Thalerosphyrus Eaton 1881 (Ephemeroptera: Heptageniidae: Ecdyonurinae) from India. 3 records from DD_cyano Targeted loci environmental. 3 records from Afrotropical Asilidae (Diptera) 18. The genus Smeryngolaphria Hermann, 1912 (Laphriinae). 1 records from New record of the genus Baetiella Uéno, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 58 records from Données du/de la naturaliste Williamson Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 20 records from Planktic foraminifera abundance of Hole 19-185. 4 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 18 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 6 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 4 records from A Catalogue and Historical Study of the Odonata of Ecuador. 1361 records from Códigos de barras de la vida en peces y zooplancton de México. 2 records from Tertiarius minutulus sp. nov. (Stephanodiscaceae, Bacillariophyta) - a new fossil diatom species from Lake Ohrid. 10 records from Description of six new large species of Argentinomyia Lynch-Arribalzaga, 1891 and redescription of Talahua fervida (Fluke, 1945) (Diptera, Syrphidae, Syrphinae). 5 records from Loricifera - SMF. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 32 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 833 records from Plant species from the sacred and community forests of Mono departement. 479121 records from KTP Ring Data. 583 records from Colección Ornitológica-Museo de Historia Natural Unillanos. 4 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 2253 records from Synthèse de la Répartition des populations de cerf élaphe en 2000 (réseau Ongulés sauvages ONCFS-FNC-FDC). 462 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 41 records from Morphologische Daten von Natrix. 1478 records from Programme FLASH : Répartition Pluvier doré 2012 - 2016 Coordonnées GPS Lambert 93. 12118 records from Soil metagenome from healthy and unhealthy agricultural soil. 3 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 46 records from Revision of the Garra species of the Hajar Mountains in Oman and the United Arab Emirates with the description of two new species (Teleostei: Cyprinidae). 12457 records from Brown University Herbarium. 103 records from Collection botanique Lamy de la Chapelle E. (BOUM). 875 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 89 records from Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 19317 records from Inventaire de la flore des Pyrénées-Atlantiques 2017 - Littoral. 95 records from BIRDRACE accipiter hardcore birding. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 71 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 23 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 1 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 17 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 1 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 712 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 2173 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 21 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 136 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 24 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 1477 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 90 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A. 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 588 records from artsprosjektet_51-14_ophiostomatoid_fungi. 201 records from Biodiversity of springs and rock seepages 2003. 10776 records from CEFS_16S_ITS. 11 records from Inventaire et regroupement de données Natura 2000. 1198 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Peces). 14 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 17 records from Analyses of the recent components of sediment core PS1219-1. 19 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 1 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 142 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 30 records from Nannofossil abundance of Hole 9-82. 2654 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 59 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 1939 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 102 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 102 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 13 records from Warnowufer Groß Klein. 153 records from Planktic foraminifera abundance of Hole 18-181. 3 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 198 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 1 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 18540 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 44032 records from Alterra (NL) - Entomofauna inventory in peat swamps. 237 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 343 records from Programme ACT : Répartition Caille des blés 2012 - 2016 Coordonnées GPS Lambert 93. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 33560 records from Extracellular DNA marine sediment Targeted Locus (Loci). 17 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 1848 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 2 records from Microfossil abundance of Hole 21-208. 200 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 896 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 1 records from Occurrence of mammalia relicts at site Ejstrup. 2041 records from marine metagenome Targeted Locus (Loci). 24493 records from Plan de vertebrados de la Patagonia. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 67 records from Planktic foraminifera distribution of sediment core TRI171-27. 12869 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 1108 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 3 records from Occurrence of mammalia relicts at site Igstadt I. 274 records from Planktic foraminifera abundance of Hole 22-217. 132 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 8 records from Nannofossil abundance of Hole 39-353A. 13000 records from LPO_PACA_2017_12_18. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 42 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 43 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 10907 records from Census of species recorded during phytosociological surveys in Benin. 724 records from Programme ACT : Répartition Faisan commun 2009 - 2013 Coordonnées GPS Lambert 93. 64 records from (Table 4) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Calabianca section. 6468 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 5364 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 41550 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 781 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 14323 records from Collection Pisces SMF. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 3 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 1584 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 36 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 4 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 242 records from Landschaftspflegehof (Berlin). 51 records from Total foraminifera counts from M35/1_MSN1051. 14368 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 74 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 356 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 2950 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 16 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 9 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 324931 records from Estonian Nature Observations Database. 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 38375 records from Botanical Museum, Copenhagen, Mycology Herbarium. 7 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 798 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 11305 records from NCSM Mammals Collection. 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 24 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 770 records from Nivå Bay species list, Zealand, Denmark. 171 records from Fungal Bioblitz in Białowieża Primeval Forest at 18th Congress of European Mycologists. 797 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 91648 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 7 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 159590 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 53 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 237 records from Avifauna asociada a humedales urbanos del municipio de Quibdó - Chocó, 2019. 3 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 19 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 86 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 6782 records from Odonata de Veracruz. 326 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 351 records from HBRG Invasive Non-native Plants Dataset. 52 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 3240 records from Inventario florístico de la Sierra de Huautla, Morelos. 1 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 186675 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 35 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil. 16253 records from Birds Specimens. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 468 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : données espèces non cibles piégées. 56 records from Planktic foraminifera abundance of Hole 23-227. 18046 records from DMNS Mammal Collection (Arctos). 43 records from (Table 9) Biological parameters of stratigraphic horizons in Core AMK7-734 according to foraminifera. 1 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 64 records from Bats of northeastern Vietnam. 1028 records from IBF Monitoring of Fungi. 231 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 4 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 2380 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 1809 records from BenthosChukchiFN762_1976_Falk5. 944 records from Fig. 4. Pollen record of profile SAO1 (Analyst: J. Hahne). 1 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 89 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 70 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 3238 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 240 records from Knechtweide (Kohlfurth). 11 records from Benthic macrofauna abundance of sediment core 12930-073. 90 records from MCP-Mamiferos - Coleção de Mamíferos. 336 records from Stable isotope data and sedimentology of core SO42-74KL. 89 records from Meniscus Midges (Dixidae) of Ireland. 1748 records from Occurrence database of native plants and animals of south-central Chile. 286 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 259 records from Natura 2000 Parc naturel régional de Lorraine. 3 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 2 records from Hangzhou-sediment-sample Raw sequence reads. 208 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 243 records from Fish species occurrences from selected near shore and riverine habitats in Lake Edward (2019). 6 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 264 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 2 records from More cautionary tales: family, generic and species synonymies of recently published taxa of ghost and mud shrimps (Decapoda: Axiidea and Gebiidea). 1751 records from Helmintos parásitos de peces del sureste de México. 383 records from Inventario de Peces del SFF Isla Malpelo, Proyecto Colombia Bio. 1 records from Two new species of Plutomurus Yosii (Collembola, Tomoceridae) from the Caucasus. 63 records from Total foraminifera counts of multinet M21/4_MSN706. 3 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 81 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 7 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 353 records from Données naturalistes de Hubert GUIMIER. 1800 records from Données de la collection Rousset -1947-2013. 399 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A. 874 records from Programme ACT : Répartition Grive musicienne 2004 - 2008 Coordonnées GPS Lambert 93. 134 records from Lynx 2005 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 87 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 133 records from Planktic foraminifera assemblage in sediment core GIK23065-2. 1 records from Schulman's Neotropical Adelobotrys database. 12094 records from Amino acid addition experiment Metagenome. 3131 records from Données DREAL Centre-Val de Loire - Faune - 2018. 45762 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 2 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 9349 records from Harriet Irving Botanical Gardens (HIBG). 46092 records from Weed and native flora data for the Swan Coastal Plain. 7 records from Revision of the genus Cobbionema Filipjev, 1922 (Nematoda, Chromadorida, Selachinematidae). 62 records from Total foraminifera counts from M35/1_MSN1061. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 9002 records from Uncultured Environmental Isolate Targeted loci environmental. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 1455 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A. 3079 records from Insectes Hyménoptères Scollidés de France. 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 4717 records from Weddell Sea macrozoobenthos EASIZ I. 1197 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 916 records from IOW Natural History & Archaeological Society Marine Records. 13 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 6189 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 14 records from Occurrence of mammalia relicts at site Climauti II. 140 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 135 records from Waldi-Weiher. 4 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 25 records from Données de NICOLAS Vincent (SAPROX). 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 493 records from Fauna and population of oribatid mites (Acari, Oribatida) in the vicinity of Kosogorsky metal works (Tula Region, Russia). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 1 records from Rhopalomenia glandulosa spec. nov., and the restoration of Entonomenia Leloup (Mollusca: Solenogastres). 6440 records from Microbial ecology of bacteiral community in sediment from adjacent waters of Rushan Bay. 77 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A. 38 records from Phytoplankton counted on two fractions of surface sediment samples from stations B-5 to B-47. 33 records from Planktic foraminifera abundance of Hole 14-144. 2572 records from seawater metagenome Metagenome. 364 records from (Table 10) Distribution of coccoliths in Core AMK7-734 from the Tajura Rift. 4372 records from Heliconiine Butterfly Collection Records from University of Cambridge. 746 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 943 records from Programme ACT : Répartition Tourterelle turque 2012 - 2016 Coordonnées GPS Lambert 93. 16 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 255 records from Tejidos colectados en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 79 records from Birdrace-Bielefinken-Bielefeld. 121 records from Range table from ostracoda in ODP Hole 143-866B. 4054 records from Fish specimens of Toyama Science Museum. 6004 records from Colección Limnológica Universidad de Antioquia. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 140770 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 4 records from Pheronema on the mid-Atlantic Ridge, data from NRCan. 3529 records from A dataset from bottom trawl survey around Taiwan. 3 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 8 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 1953 records from Coral Reef Evaluation and Monitoring Project Florida Keys 1998. 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 191 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 5 records from Copepoda (Siphonostomatoida: Dirivultidae) from Hydrothermal Vent Fields on the Central Indian Ridge, Indian Ocean. 14 records from (Table 4b) Biomass of Emiliania huxleyi and its role in total biomass of phytoplankton along the section from the Pribilofs Islands to the Nunivak Island on 24-25 August 2001. 12 records from Lepidoptera specimen database of Japan. 294817 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations. 37 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 130 records from BIRDRACE - The famous Grouse feat. The James. 356 records from Planktic foraminifera abundance of Hole 68-503B. 63 records from Distribution of meiofauna in surface sediments of the Iberian deep sea basin (Table 3). 183 records from Relative abundance of ostracods in sediment core Sv09. 48 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 185 records from Inventaire des odonates d'intérêt communautaire. 149 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 1893 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 2419 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 101 records from Radiolaria assemblage in sediment core GIK23400-3. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 685 records from Range table from benthic foraminifers in ODP Hole 151-913B. 198 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 259 records from Programme ACT : Répartition Alouette lulu 2009 - 2013 Coordonnées GPS Lambert 93. 2102 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 124 records from Kirkliston Range stream monitoring. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 3 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 16838 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 7839 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 5316 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 5 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 84 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 2933 records from Données naturalistes d'Alain BERLY. 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 27676 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 368 records from Ring ouzel national sample survey in the UK in 1999. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 250 records from Inventaire et regroupement de données Natura 2000. 61 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 12722 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 637617 records from Données de la flore d’Alsace (SBA). 486 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 2 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 696 records from the diversity of anammox bacteria in the subterranean estuary. 160 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 26185 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 384 records from Nannofossil abundance of Hole 17-167. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 176 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 110497 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 423 records from Programme ACT : Répartition Caille des blés 2008 - 2012 Coordonnées GPS Lambert 93. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 1559372 records from Flore Franco-Belge. 1477 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 16443 records from EAC - Herbário Prisco Bezerra. 1485 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1531 records from Leif Richardson Vermont Bee Specimens. 9 records from PRA Sonneur à ventre jaune - étude de répartition. 63 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 8901 records from Collection Crustacea - ZMB. 740 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 4 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 8 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 521 records from Schanzenanlage Bergham. 140 records from Planktic foraminifera abundance of Hole 37-332. 74 records from Reptiles de la expedición al Río Apaporis - Proyecto Colombia BIO. 833 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C. 170 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 72 records from Total foraminifera counts of multinet POS231/3_MSN1332. 961 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 25 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 395 records from Nannofossil abundance of Hole 37-334. 59 records from Schulgelände SGD/Viersen. 1533 records from Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 69 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1293 records from Flora genérica de las gramíneas del estado de Tlaxcala. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 5464 records from Natural History Museum Maastricht (NL) - Herbarium. 9384 records from MZL Invertebrate Collections. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 352 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 11 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 161 records from Total foraminifera counts of multinet SO117_MSN1244. 485 records from Rothschild Giraffe occurrence records observed at Mwea National Reserve in Central part of Kenya. 8956 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 6 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 6990 records from Ethnobotanical surveys species in Benin (West Africa). 87 records from Hidden gems in museum cabinets: new species and new distributional records of Scolytodes (Coleoptera: Scolytinae). 136 records from Inventaire faunistique de l'ENS des Parc des berges de Seine. 3 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 5576 records from uncultured prokaryote Targeted loci environmental. 3435 records from Benthos Chirnov Basin 1986 and 2002. 6 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 6387 records from Données naturalistes de Monsieur LAFAGE Denis. 51 records from Coccoliths in sediment core GIK23065-3. 5 records from On the genera Ptiloneura Enderlein, Loneura Navás, and Loneuroides García Aldrete (Psocodea: ‘ Psocoptera’: Ptiloneuridae). 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 133 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 15 records from A review of the bats (Chiroptera) of the Republic of Congo, including eight species new to the country. 90 records from Actualización de la base de datos de la Colección nacional mexicana de cultivos microbianos. 2141 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 5818 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 781 records from Ecological study of the plankton in the port of Ostend in 1965. 192 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 93324 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 14 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 49 records from Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 4142 records from Trondheim urban biodyversity survey. 94 records from Données du/de la naturaliste LUSTRAT Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 142 records from Size of planktic foraminifera at CTD station PS55/083-1. 58 records from Swedish Malaise Trap Project (SMTP) - Banchini. 303 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 34525 records from R. L. McGregor Herbarium Lichen Collection. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 12 records from A revision of the spider genus Anemesia (Araneae, Cyrtaucheniidae). 200 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 557 records from Corn bunting breeding distribution in Scotland. 919 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 71 records from Foraminifera species abundances from tow TT007_7-MOC13. 336 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 4 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 2 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 40011 records from Banded Iron Formation and Greenstone survey data. 4 records from New records and checklist of Chilocorini (Coleoptera: Coccinellidae) from China. 38 records from Microzooplankton abundance and biomass at station TT045_19-3. 1 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 30 records from Feral Pigs - Sightings and Cull records - 2014-2015. 131 records from Occurrence of mammalia relicts at site Bocksteinschmiede. 51 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 18 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 30 records from Range table from planktonic foraminifers in ODP Hole 178-1096A. 1894 records from Fungi Collection. 2 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 87 records from Données espèces - Expertise IPE 70. 12 records from Two new genera and three new subterranean species of Hydrobiidae (Caenogastropoda: Truncatelloidea) from Tunisia. 940 records from NOAA coral reef monitoring invertebrate data from sites across Micronesia from 2009-09-29 to 2015-09-25. 20 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 3 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 30954 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 152 records from Plasm bearing foraminifera counts from multinet SO119_MSN1281. 121 records from Total foraminifera counts of multinet M10/2_MSN262. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 98 records from Description of lithologic section units of IODP Hole 325-M0033A. 84312 records from NE AVH data. 21 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 46 records from Total foraminifera counts of multinet M21/5_MSN742. 47 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 282 records from Deponie Klausdorf. 48 records from Schulgelände (Wetter). 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 55 records from Phytoplankton abundance at station Casma_2003-04-28_2, Casma, Peru. 22817 records from Floristische Kartierung Österreichs - Mapping the Flora of Austria. 4923 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 1986 records from Observations de Coléoptères saproxyliques de Frédéric LACOSTE. 2 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 29 records from Benthic foraminifera abundance of Hole 42-379A. 1489 records from Population research on small rodents (Rodentia) and screws (Soridae) in Steinkjer Municipality – Norway; 2018 - 2019 based on systematic catches with ordinary mouse traps in traplines. 1462 records from (Table 3) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-657A. 2548 records from BioGIS - Reptiles - HUJ collections. 13 records from Analyses of the recent components of sediment core PS1222-1. 901635 records from Flora Atlas N.T.. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 3 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 2 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 12 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 2 records from Two new species of Hetereleotris (Perciformes: Gobiidae) from the Red Sea. 129 records from Données du/de la naturaliste jourdan christian provenant de la base de donnée du SINP Île-de-France CETTIA. 147 records from Revision of the spider genus Hoplopholcus Kulczyński (Araneae, Pholcidae). 754 records from Programme ACT : Répartition Grive draine 2001 - 2005 Coordonnées GPS Lambert 93. 1856 records from Analysis of macrobenthos in the Southern Bight of the North Sea (1971-1972). 990 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 10 records from Ostracoda abundance of Hole 32-306. 244 records from Nannofossil abundance of Hole 29-281. 3856 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 314 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 13 records from Range table from planktonic foraminifers in ODP Hole 139-856C. 580 records from Rare plants database extract from Scottish Natural Heritage. 68377 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 27191 records from Formidabel; Belgian Ants Database. 1148 records from ABC event data for Nyika Plateau, Buma Hills. 126 records from Range table from planktonic foraminifers in ODP Hole 167-1021B. 55 records from Macroinvertebrados bentónicos de playas de arena (Monte Hermoso-Pehuen Có, Buenos Aires, Argentina). 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 5586 records from (Table 1) Ranges of Paleocene to middle Eocene planktonic foraminifera in ODP Hole 119-738B. 119 records from Suivi des leucorrines sur le site du Marais du Plata. 127 records from Сypripedium guttatum Sw. in the Komi republic. 146 records from Abundance of birds in the Lena Delta Region. 79 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 31 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 435 records from Synthèse de la Répartition des populations de chamois en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC). 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 35 records from Ortsrand Zandershagen. 69 records from artsprosjektet_48-13_monomyx. 39 records from Planktic foraminifera counts of sediment core V19-21. 1188 records from (Figure 10) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-631A. 1 records from Occurrence of mammalia relicts at site Ballybetagh. 5360 records from Colección Ornitológica de la Universidad del Valle. 338 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Privolzhskaya Lesostep. 10 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 1 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 188 records from Données de Mammifères marins. Mission Sanctuaire AGOA de 2012 à 2014. 576 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 224 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-017. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 159 records from Total foraminifera counts from multinet M31/3_MSN915. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 41676 records from Tagged Seal Location Data from SOGLOBEC. 333 records from Données naturalistes de Renaud PUISSAUVE. 842 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 1 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 3230 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 1709 records from The Gibson spider collection. 56 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 918 records from (Fig. 1) Ice rafted debris and planktic foraminifers of Hole 94-609. 651 records from Réseaux écologiques/Trame verte et bleue. 14 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 236282 records from Wild bees of Belgium. 422108 records from NOAA AFSC North Pacific Groundfish Observer. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 16 records from Hazel Dormouse in Ireland. 106 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 272 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 1027 records from Programme ACT : Répartition Merle noir 1996 - 2000 Coordonnées GPS Lambert 93. 7 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 115 records from Total foraminifera counts of multinet M21/4_MSN694. 46 records from An der Ohm, (Wettsaasen). 294 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 22 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 536 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 1 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 6 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 74 records from Anfibiofauna asociada a la quebrada Giginia, corregimiento de Doña Josefa, Municipio del Atrato - Chocó, 2019. 52 records from Occurrence of mammalia relicts at site Goyet Cave 3. 37 records from FBIP: scallop population genetics. 18 records from Schulgarten der Gesamtschule Am Heidberg. 1270 records from Données du/de la naturaliste Lantz André provenant de la base de donnée du SINP Île-de-France CETTIA. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 62 records from Données naturalistes de BONCHE Jérôme. 28 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 304 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 79759 records from natagora-earlybirds. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 8985 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 18 records from Range table from planktonic foraminifers in ODP Hole 167-1010B. 29 records from Reptiles Specimens of Akita Prefectural Museum. 338 records from UWIZM Snakes. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 182 records from Tejidos colectados en el piedemonte llanero, Boyacá - Proyecto Boyacá BIO. 145 records from Biodiversity survey of Rugezi wetland, Year 2013. 449 records from Artsprosjekt Pyrenomycetes. 6654 records from NOAA coral reef monitoring benthic data from sites across Micronesia from 2009-09-29 to 2015-09-25. 121 records from Etude écologique du Parc des Lilas (94). 12 records from Données bibliographiques ASFRA. 7953 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 1 records from A new Aceria species (Acari: Prostigmata: Eriophyoidea) from Minuartia frutescens (Caryophyllaceae) in Hungary. 17 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 2340 records from Butterflies_of_Singapore_and_Peninsular_Malaysia_(Nymphalidae). 7510 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 254 records from Atlantic Forestry Centre Insect Reference Collection. 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 3 records from A new species of Flavoperla Chu, 1929 (Plecoptera: Perlidae) from Guangxi Zhuang Autonomous Region of southern China. 4727 records from Dataflos. 9 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 2743 records from marine sediment metagenome Raw sequence reads. 28 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 247 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325. 2095 records from (Table 1) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 74-525A from the Walvis Ridge, South Atlantic Ocean. 55 records from Occurrence of mammalia relicts at site Rusenschloß. 75 records from Plasm bearing foraminifera counts of multinet M21/5_MSN730. 9 records from Benthic macrofauna abundance of sediment core 12930-048. 96 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1381. 1211 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 11 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 48 records from Content of coarse fraction and G. menardii in sediment corev V25-44. 162 records from (Table 6) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-216. 615 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 1 records from A new, peculiar genus of Cossoninae (Coleoptera, Curculionidae) from Oman with description of a new species, larva and notes on biology. 40738 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 15251 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 1 records from Diversity of methyl alkyl succinate synthase genes in hydrocarbon seep sediments (Raw sequence reads). 1 records from Labrys khuzestanensis n. sp. (Nematoda, Tylenchidae), a new member of the genus with large labial plate. 13 records from Lane 6 Analysis. 3939 records from Census of plant species in Pahou forest reserve. 3 records from A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia). 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 6578 records from Ibaraki Nature Museum, Fungi collection. 911 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 54 records from Données du/de la naturaliste Villalta Rémi provenant de la base de donnée du SINP Île-de-France CETTIA. 22 records from Observations de tortues marines dans l'archipel de Saint-Pierre et Miquelon. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 1450 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 874 records from (Table 1) Calcareous nannofossil distribution and relative abundance in ODP Hole 114-699A. 48 records from Total foraminifera counts of multinet M6/7_MSN140. 9740 records from Royal British Columbia Museum Entomology Collection. 33 records from Dinoflagellate abundance of Hole 81-552. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 2800 records from Mid-Pleistocene (800-400 ka) planktic foraminfer assemblages of IODP Site 306-U1314. 8 records from A review of the Neotropical microcaddisfly genus Acostatrichia Mosely, 1939 with description of a new species from Brazil (Trichoptera: Hydroptilidae: Leucotrichiinae). 5938 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 8367 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 143 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 6 records from NZCS Invertebrates New Collection After 1987. 2985 records from Colección Entomológica CDMB. 16929 records from Lepidoptera (Specimens NRM). 198 records from Chronicle of Nature - Phenology of Birds of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 822 records from Las comunidades de myxomicetes de selva baja caducifolia. 27799 records from Collection of saproxylic and xylobiont Beetles. 781 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 110 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 415 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 22122 records from Tachinid Recording Scheme - GB and Ireland records. 3 records from Denitrification bacteria in sediment cores of Daya Bay, China. 5 records from Thoridae (Crustacea: Decapoda) can penetrate the Abyss: a new species of Lebbeus from the Sea of Okhotsk, representing the deepest record of the family. 6 records from Five new species of Nazeris Fauvel in Guangxi, China (Coleoptera, Staphylinidae, Paederinae). 5 records from Données naturalistes de Mikaël PAILLET. 4607 records from Données de type contact en Guadeloupe. 79 records from New records of Ichneumonidae (Hymenoptera) for the Italian fauna. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_5-CTD58. 130 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 29 records from Planktic foraminifera assemblage in sediment core GIK23243-2. 4 records from A new, uniquely patterned spiny eel (Teleostei: Mastacembelidae) from southern Borneo, Kalimantan Tengah, Indonesia. 55 records from Galls on Beech Trees in Hainich, 2008. 6 records from New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae) from Colombia, with an identification key for all known species of the genus. 31 records from Ecosystems of the sandstone region incl. sand-belt (SE of Melb.). 8 records from A new species of Cetopsis from the Guiana Shield (Siluriformes: Cetopsidae: Cetopsinae). 640 records from Annales de la Société Linnéenne de Maine-et-Loire. 1722 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 12452 records from Insectes Hétéroptères Mirides de France. 3 records from Taxonomic notes on the tribe Dryptini Bonelli, 1810 with description of a new genus and species from China (Coleoptera: Carabidae: Dryptini). 354 records from Programme ACT : Répartition Caille des blés 2000 - 2004 Coordonnées GPS Lambert 93. 618 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 618 records from Pollen analysis of sediment core GeoB6518-1. 494194 records from BLS Mapping Scheme dataset, 1750-2009. 1114 records from Chronicle of Nature - Phenology of Plants of Kronotsky Federal Nature Biosphere Reserve. 13 records from New plant associations for adults of some species of Acmaeodera Eschscholtz (Coleoptera: Buprestidae) occurring in the western United States. 41 records from Relative abundance of planktic foraminifera in sediment core K11. 27 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 656 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 275 records from Composición florística de áreas degradadas por actividad minera a cielo abierto en el municipio de Condoto-Chocó, como insumo para calcular la biomasa vegetal, 2017. 1 records from Planktic foraminifera abundance of Hole 54-420A. 40135 records from DIBA-Parc del Montnegre i el Corredor. 21 records from Caracterización de la epifauna y macrobentos (0-800 m) de Isla Cayo Serranilla y Áreas aledañas: Equinodermos primera fase 2017 - Proyecto Colombia Bio. 4755 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 1 records from Re-description of Grammapsychops lebedevi Martynova, 1954 (Neuroptera: Psychopsidae) with notes on the Late Cretaceous psychopsoids. 53 records from Description of lithologic section units of IODP Hole 325-M0043A. 7 records from Grundwasserlebensraum im Englischen Garten (München). 1993 records from Inventario de macroalgas de Isla Guadalupe, México. 213 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 830 records from Invertebrados del Parque Nacional Arrecife Puerto Morelos. 3 records from Description of a new species of the Rhinolophus trifoliatus-group (Chiroptera: Rhinolophidae) from Southeast Asia. 19 records from Nesting biology and distribution of Stenancistrocerus (Paratropancistrocerus) obstrictus (Morawitz, 1895) (Hymenoptera: Vespidae: Eumeninae). 753 records from Colección de insectos de importancia médica del Instituto Nacional de Salud - Ceratopogonidae. 8041 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 2873 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología (Mexicanos). 3 records from Prosoglypta, a new remarkable genus from Vietnam (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 720 records from Données du naturaliste Bussac Augustin provenant de la base de donnée du SINP Île-de-France CETTIA. 983 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 40 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 44050 records from Données naturalistes de Pascal Dupont. 18 records from suivi du site Natura 2000 Carrière Saint Nicolas. 134 records from Faunal assemblage of sediment core GS7603-13. 2170 records from Inventaire des sangsues - détermination prélèvements de bureau d'études (qualité de l'eau) - Subvention UMS Patrinat. 2 records from Wie viel Natur gibt es im Park?. 1764 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 2 records from A new species of the fishfly genus Neochauliodes van der Weele (Megaloptera Corydalidae) from India. 1082 records from Zootaxa. 2297 records from Colección de Anfibios. 10984 records from NBMB Herps. 386 records from Foraminifera distribution of sediment core KS310. 11131 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 3018 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 94 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 2970 records from Distribution patterns of subtidal macrobenthos in the Tsitsikamma National Park. 104 records from (Table 3) Abundance and biomass of Proboscia alata in patches of its mass development over the Bering Sea middle shelf, percentages of P. alata and associated algae species and their groups in total phytoplankton abundance and biomass. 405 records from NHMO DNA Bank Other groups collection. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 11 records from Barsine insolita, a new species from Indochina and India (Lepidoptera, Erebidae, Arctiinae). 42 records from DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 3 records from El género Aleuroparadoxus Quaintance y Baker 1914, con descripción de tres nuevas especies, nuevos registros y clave para las especies (Hemiptera: Aleyrodidae). 2 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 463 records from Damselflies of the genus Argia (Odonata: Coenagrionidae) from Ecuador with descriptions of five new species. 3 records from Description of Bradinopyga konkanensis sp. nov. (Odonata: Anisoptera Libellulidae) from the coastal region of Maharashtra, India. 192338 records from University of Michigan Museum of Zoology, Division of Birds. 811 records from Données naturalistes de AUNEAU Florent. 1806 records from uncultured marine picoeukaryote strain:Peuk_V4_NWP2 Raw sequence reads. 567 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 5 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 363 records from (App 1) Relative contents of mass species of benthic foraminifera in Holocene sediments from Core ASV11-880-3. 408 records from Collection Graptolithina fossil SMF. 10 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 25934 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 10 records from Talitrid amphipods from India, East Africa and the Red Sea (Amphipoda, Senticaudata, Talitroidea, Talitridae). 11 records from Suphisellus grossoi sp. n., a new burrowing water beetle from South America and notes on S. flavolineatus (Régimbart, 1889) and S. grammicus (Sharp, 1882) (Coleoptera: Noteridae). 62 records from Zoo Frankfurt. 203 records from Estrategia de conservación de grandes felinos en el departamento del Meta. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 1085517 records from Fungal Records Database of Britain and Ireland. 738 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 237 records from Capercaillie national surveys. 61645 records from La familia Asteraceae en México. Fase VI. 555 records from (Table 3) Protist occurrence in bottom sea ice and surface water samples obtained during a CCGS Amundsen cruise in 2007/2008. 63 records from Marine gastropod distribution from patagonian shallow waters. 128 records from Données espèces - Expertise IPE 10. 1 records from Species delimitations in the Atractus collaris complex (Serpentes: Dipsadidae). 19 records from New species of Otiothopinae (Araneae: Palpimanidae) from Colombia. 3766 records from Benthic foraminifera distribution of sediment core GIK17957-2. 4 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 12487 records from Florida Keys Reef Visual Census 1996. 1 records from Off the scale: a new species of fishscale gecko (Squamata: Gekkonidae: Geckolepis) with exceptionally large scales. 2 records from Potamocloeon edentatum sp. n. from Usambara Mountains in Tanzania (Ephemeroptera, Baetidae). 1625 records from Molluscan specimens from the Astrolabe Reefs (Kadavu, Fiji), 1986-2006. 50 records from Antractic whale observation on a platform of opportunity abroad krill fishing vessel "Dalmor II", April - July 2011.. 621 records from BID-Malawi-Geometridae-Biodiversity-Data. 12 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 636 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 26 records from Stable carbon and oxygen isotope record of Cretaceous planktonic foraminifera from DSDP (Table 1). 228 records from JOI - Herbário Joinvillea. 27 records from A revision of the African wolf spider genus Amblyothele Simon. 20 records from Occurrence of mammalia relicts at site Tokod-Nagyberek. 1 records from A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India. 6247 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 81 records from Birdrace-Die_Ornithomaten-Herford. 4 records from First record of the millipede genus Nesorthomorpha Jeekel, 1980 in Vietnam with description of a new species (Diplopoda, Polydesmida, Paradoxosomatidae). 1 records from A new genus and species of Apameini (Lepidoptera: Noctuidae) from Sichuan (China). 1080 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 103 records from Mammals (UWEP-MM). 84980 records from NINA Vanndata fisk. 1 records from A new species of Coleophora (Lepidoptera: Coleophoridae: Coleophorinae) from the Galápagos Islands, Ecuador. 510 records from Inventaires des cygnes du département de l'Eure. 25 records from Herpetofauna de la expedición Piedemonte Llanero - Proyecto Boyacá BIO UPTC. 96 records from Peces de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 53062 records from British Antarctic Survey Argos satellite tracking data. 230880 records from Soil bacterial diversity is associated with human population density in urban greenspaces. 3 records from Distribution of meiobenthos in sediment core M19_217-2 of the northeastern Atlantic (Table 1). 113 records from Total foraminifera counts of multinet M26/1_MSN844. 4 records from Microplankton abundance at bottle station SEPT-1999-K4. 7 records from Taiwanese deep-water chitons (Mollusca: Polyplacophora) and survey of chiton fauna of Taiwan. 3125 records from (Table 3) Occurrences of diatoms species in DSDP Hole 41-369A. 583 records from Données du naturaliste Christian Desmier. 27267 records from (Table 2) Mollusc biostratigraphy of facies underlying the 'Braunkohlensande' in the Lauenburg district, north Germany. 9 records from New species of Glossoscolex and Fimoscolex earthworms (Oligochaeta: Glossoscolecidae) from Embrapa Forestry, Paraná, Brazil. 836 records from Odoanta of Akwa Ibom State University, Nigeria. 1135 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 192 records from Diversidad y conservación del germoplasma de henequén Agave fourcroydes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 11884 records from Données naturalistes de Franck NOEL. 364 records from Natura 2000 ZPS Jarny - Mars-la-Tour. 2369 records from Chronicle of Nature - Phenology of Birds of Darwin Nature Biosphere Reserve. 5695 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 111 records from Review of Afrotropical Glenosema Kieffer (Hymenoptera, Bethylidae) with description of 13 new species. 119353 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 13 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-104BX. 5934 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 176 records from Planktic foraminifera abundance of Hole 94-610B. 70 records from (Table 4) Coiling direction changes of Neogloboquadrina acostaensis during the latest Miocene and early Pliocene of DSDP Hole 94-608 from the North Atlantic Ocean. 113 records from Arizona State University Lois B. O'Brien Collection. 2082 records from Registros biológicos de flora para el desarrollo de acciones de evaluación, seguimiento y monitoreo en los elementos priorizados de la estructura ecológica principal del distrito capital. Bogotá D.C.. 52 records from Occurrence of mammalia relicts at site Zigeunerfels. 2 records from Description of lithologic section units of IODP Hole 325-M0052C. 47 records from Black Corals (Anthozoa: Antipatharia) from the Southwestern Atlantic. 7178 records from Ravensthorpe Range survey data. 56 records from Ictiofauna balseana y helmintos parásitos asociados. 5 records from Scorpaena regina, a new scorpionfish (Teleostei: Scorpaenidae) from the east coast of Queensland, Australia. 5 records from Schulinnenhöfe (Gelsenkirchen). 395 records from (Table 2) Some abiotic factors and distribution of benthic foraminifers in surface layer of bottom sediments from the littoral zone of the Kunashir Island (Pacific Ocean side). 12 records from Analyses of the recent components in the sand fraction of sediment core PS1012-1. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 31 records from Nanoplankton abundance at station GeoB2012-5. 841 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 7484 records from Yoann_BLANCHON_2017_12_18. 1 records from Notes on the genus Gargela (Lepidoptera: Crambidae) ı with descriptions of two new species from China. 1012 records from Programme ACT : Répartition Merle noir 2000 - 2004. 3 records from MSB Mammal Observations (Arctos). 10 records from Données naturalistes de Sophie COHEN. 2126593 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 53 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB03 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 20068 records from Wikiplantbase #Sicilia. 2 records from The spider wasp genus Telostholus Haupt, 1929 (Hymenoptera, Pompilidae) in Malaysia, with the description of four new species. 1879 records from Database of Australasian Vertebrate Occurrences. 498 records from Bekkelag basin, Inner Oslofjord. 215 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 4 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 748 records from Phenological Center - Birds (Laplandskiy). 551 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 609 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1994. 57 records from Inventaire faune flore de l'étang d'Abbecourt à Orgeval. 48 records from Benthic foraminifera abundance of Hole 42-380. 1010731 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 60 records from (Table 2) Palynomorph concentrations in ODP Hole 105-647A samples. 58 records from Composition of the smaller coarse silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 29105 records from Marine Biological Sample Database, JAMSTEC. 330 records from Otter (Lutra lutra), Outer Hebrides. 743 records from Insectos recolectados en trampas Malaise en el departamento de Antioquia - Proyecto Colombia Bio. 416 records from The Living Murray Fish data. 4428 records from "Categorization of the wild food plants and their importance for primate development in the natural forest of Akpe (Lama) in southern Benin.". 25974 records from Long-term Bird Census in Cigu 2004-2017. 7 records from Contribution to the AIrotropical Ɨchneumoninae (Hymenoptera, Ɨchneumonidae) Irom Gabon and Sierra Leone, with descriptions oI Iive new species and two new subspecies. 4 records from Range table from planktonic foraminifers in ODP Hole 159-960A. 1084 records from Distribution of foraminiferal fauna from ODP Hole 122-762C (Table 1). 240 records from BARTH-Environnement_2017_12_18. 15 records from Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae). 325 records from Study of epibenthos and demersal fish in and around the thiocarbamate discharge area of the Belgian Continental Shelf (1977-1981). 156 records from Total foraminifera counts of multinet M21/2_MSN658. 34 records from Microzooplankton abundance and biomass at station TT043_11-1. 1956 records from Colección de Entomología - Hymenoptera - Chalcidoidea. 101 records from BIRDRACE Enger am Spektiv. 79 records from Swedish Malaise Trap Project (SMTP) - Syrphidae. 1377 records from Ghent university - Zoology Museum - Nematod Collection. 32 records from Sciapodinae from the Himalayan region with description of nine new species from Tibet (Diptera: Dolichopodidae). 125 records from Total foraminifera counts from multinet M32/3_MSN956. 6164 records from Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 10 records from Données naturalistes de CLERGET sylvie. 2 records from A new genus and species of grasshopper from China (Orthoptera: Acrididae Catantopinae). 7 records from Stadtrandlandschaft Apolda-Nord. 12 records from Microzooplankton abundance and biomass at station NBP97-03-13-2. 40 records from Calliostomatidae, Colloniidae, Margaritidae, and Solariellidae (Gastropoda: Trochoidea) collected by the Marion Dufresne (MD 55) expedition in southeastern Brazil, with description of a new species of Calliostoma. 5 records from A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from India. 2 records from First description of male of the type species Parosmylus prominens Needham, 1909 (Neuroptera: Osmylidae) from India. 7 records from Notes on slender species of the long-jawed spider genus Tetragnatha (Araneae Tetragnathidae) with description of three new species. 3230 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 61547 records from Florida Keys Reef Visual Census 2010. 153 records from annex1. 123 records from Total foraminifera counts of multinet POS247/2_MSN1377. 28 records from Dinoflagellate abundance of Hole 28-270. 2 records from Review of Allanagrus Noyes & Valentine (Hymenoptera: Mymaridae) with a key to species. 693 records from (Table 1) Distribution of Lower Cretaceous calcareous nannofossils at DSDP Hole 93-603B. 62 records from Rare vascular plant species in North-West of Kostroma region, Russia. 2 records from A synopsis of the subgenus Centris (Hemisiella) Moure, 1945 (Hymenoptera: Apidae: Centridini) in Colombia, with description of a new species. 5069 records from Données mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 2. 18 records from Sarcodine counts and carbon biomass at station TT008_6-PMOC7. 204 records from (Abb. 8 bot) Pollen profile Radauerborn, Harz. 16 records from Dinoflagellate cysts of surface sediments. 5 records from Collection Malakologie - SMNG. 50 records from Données d'observation de phanérogames marines en Martinique. 1721 records from Phytoplankton data collected from the Black Sea during November 1957 (Cruise 2). 1 records from Rocky-intertidal cheilostome bryozoans from the vicinity of the Sesoko Biological Station, west-central Okinawa, Japan. 374 records from Coastal and Marine Species Database. 145 records from Nannofossil abundance of Hole 67-499. 900 records from Convention Fédération française de golf - MNHN 2016-2019.. 224 records from Données du naturaliste DESCHATRE Thierry provenant de la base de donnée du SINP Île-de-France CETTIA. 587 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 222 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 6080 records from Sepsidae (Diptera) records from Britain and Ireland to 1985. 9 records from UTEP Fish (Arctos). 5 records from A review of Gonothrombium Feider, 1950 (Actinotrichida: Microtrombidiidae) with description of a new species from Turkey. 79 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Pompo) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 138 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 1 records from A new species of Anthiadinae (Teleostei: Serranidae) from São Pedro and São Paulo Archipelago, Brazil, Equatorial Atlantic.. 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 1066 records from Territorial Andes Occidentales - Densidad poblacional VOC subsistema cámaras trampa, 2018. 1 records from A review of the species of Anaspis (s. str.) similar to A. nigripes Brisout and A. apfelbecki Schilsky, with the description of three new species (Coleoptera: Scraptiidae). 4306 records from Saproxylic and herbivorous beetle species in old near-natural and old managed forests in south-eastern Norway. 2 records from A new subspecies of Zamenis hohenackeri (Strauch, 1873) (Serpentes: Colubridae) based on morphological and molecular data. 29 records from A review of the Cyana bianca (Walker, 1856) species-group with descriptions of a new species and a new subspecies from Indochina (Lepidoptera, Erebidae, Arctiinae). 810 records from Environmental long read amplicons of soil fungi across Podzol soil profile. 2 records from A revision of the Australian species of the genus Melobasis Laporte & Gory 1837 (Coleoptera: Buprestidae), Part 2 (Revision of the nervosa species group). 8 records from Four new and three newly recorded species of Diduga Moore, [1887] (Lepidoptera Erebidae, Arctiinae) from China. 3687 records from Clare Biological Records Centre Dataset 2004-2007. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 2 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 4 records from A new glass sponge genus (Hexactinellida: Euplectellidae) from abyssal depth of the Yap Trench, northwestern Pacific Ocean. 25765 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 2 records from Two new species of the genus Crangonyx Bate, 1859 (Amphipoda: Crangonyctidae) from the St. Marks River Basin with notes on the “ Crangonyx floridanus complex ”. 174 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas?. 3 records from The genera Agelosus Sharp, 1889 and Apecholinus Bernhauer, 1933 in Taiwan (Coleoptera: Staphylinidae: Staphylinini: Staphylinina). 20 records from Truchas Mexicanas. 13639 records from Senckenberg - CeDAMar Resource. 51 records from Marine metagenome ICM_VAG. 1 records from On the taxonomy of Lygosoma bampfyldei Bartlett, 1895 (Squamata: Scincidae) with descriptions of new species from Borneo and Peninsular Malaysia and the resurrection of Lygosoma schneideri Werner, 1900. 564 records from Biological Collection, National Institute of Oceanography, Goa, India. 1579 records from Occurrence data set for wild food plant species in Zimbabwe's biodiversity hotspots. 1002 records from ABC_Useful Plants of Malawi: Species used as Herbal aphrodisiacs. 93 records from A revision of the genus Mesoconius Enderlein (Diptera, Micropezidae, Taeniapterinae). 16 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 90 records from (Table 3) Abundance of living foraminifers in bottom sediments from the Kandalaksha Bay. 93 records from Données du/de la naturaliste Fourrier Thibault provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Planktic foraminifera abundance of Hole 54-428. 282 records from Ichthyofauna of the Kubo, Tochikura, and Ichinono river systems (Kitakami River drainage, northern Japan), with a comparison of predicted and surveyed species richness. 1 records from Family, generic and species synonymies of recently published taxa of ghost shrimps (Decapoda, Axiidea, Eucalliacidae and Ctenochelidae): cautionary tales. 11 records from Benthic macrofauna abundance of sediment core 13200-045. 1694 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 2216 records from Monitoreo de la población de la guacamaya verde en la Reserva de la Biosfera Tehuacán-Cuicatlán. 1054 records from Aves de la cuenca alta y media del río Bita, (Vichada) Colombia. 265 records from (Table 3) Occurrence of benthic foraminifers in ODP Hole 116-718C. 2 records from Two new Isotomidae species (Collembola) from Espírito Santo State, Brazil. 1 records from The Cat-eyed Snakes of Madagascar: Phylogeny and Description of a New Species of Madagascarophis (Serpentes: Lamprophiidae) from the Tsingy of Ankarana. 2336 records from (App 8) Relative contents of planktonic foraminifera species in sediments from Core GeoB3011-2. 2000 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 1 records from A new genus and new species of freshwater crab (Decapoda: Brachyura: Potamidae Ortmann, 1896) from Yunnan Province, China. 7 records from Insect specimens of Himeji City Science Museum. 80 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 148 (N.S) n° 41 (1), 2013 - Données faune. 2282 records from Ohio University Invertebrate Paleontology Collection. 3363 records from (Table 13) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-591. 2 records from Four new species of Phyllophaga Harris (Coleoptera: Scarabaeidae: Melolonthinae) from western Cuba. 1 records from Description of the female of Chelis ferghana Dubatolov, 1988, an endemic moth species of the Tien Shan Range in Central Asia (Lepidoptera: Erebidae Arctiinae). 28 records from Occurrence of mammalia relicts at site Bettelküche. 33318 records from BrioCAT: Banco de datos de los briòfitos de Cataluña. 147 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/049-3. 347 records from Données de la structure Département 78 provenant de la base de donnée du SINP Île-de-France CETTIA. 6107 records from (Table 3) Planktonic foraminifers from ODP Hole 114-704A. 1338 records from Abundance of algae in the Aral Sea. 29 records from Naturerfahrung. 53 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 158 records from Total foraminifera counts from M35/1_MSN1047. 948 records from Données naturalistes de Damien Combrisson. 2214 records from Range table from benthic foraminifers in ODP Hole 159-962D. 19 records from Suivi des reptiles des landes du Technopôle du Madrillet. 140 records from Total foraminifera counts of multinet M12/3_MSN535. 896 records from Data on agroforestry plant species of Benin. 4454 records from Insectes Hyménoptères Formicidés de Corse. 29 records from Données malacologiques du site Natura 2000 de Cessière-Montbavin. 2569 records from Radiolaria specimens from Korsfjorden Nov 1969 - May 1971. 224 records from The Avian Collection of the Tana River Basin at the National Museums of Kenya's Ornithology Section.. 3458 records from Base de datos de la Sala de Colecciones Biológicas de la Universidad Católica del Norte (SCBUCN). 5621 records from Plan d'Aménagement participative de la Forêt Classée d'Alédjo (Togo). 11 records from Benthic macrofauna abundance of sediment core 13078-013. 1127 records from Planktic foraminifera counts of sediment core RC14-35. 2 records from A new species of Aoruroides Travassos & Kloss, 1958 (Nematoda: Oxyuridomorpha Thelastomatidae) parasite of the wood-burrowing cockroach Panesthia angustipennis spadica (Shiraki, 1906) (Blattodea: Blaberidae: Panesthiinae) from Japan with comments on the validity of the genus Aoruroides. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 29 records from Taxonomic notes on Palearctic Podalonia Fernald, 1927 (Hymenoptera, Sphecidae), with descriptions of four new species. 1296 records from Avifauna de los Parques Ecológicos Distritales de Montaña del Distrito Capital. 21 records from New species and record of Nazeris Fauvel in southern China (Coleoptera, Staphylinidae, Paederinae). 661 records from Données espèces Expertise IQE 311. 168 records from Microplankton abundance in the euphotic zone of the Aegean Sea in October-November 1991. 2550 records from Nematode genera abundance from Portuguese canyons HERMES HERMIONE. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN734. 1 records from Tyrannosaurus rex from the McRae Formation (Lancian, Upper Cretaceous), Elephant Butte Resevoir, Sierra County, New Mexico. 21 records from (Tab. 2) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 1-4, Blake-Bahama Basin. 28214 records from India Biodiversity Portal publication grade dataset. 3083 records from Butterflies_of_Singapore_and_Peninsular_Malaysia_(Lycaenidae). 574 records from (Appendix 2) Diversity and foraminifera of sediment core M5/2_KL15. 3 records from New species of the spider genus Olios Walckenaer, 1837 (Araneae: Sparassidae: Sparassinae) from Laos. 257 records from Determinación de la distribución potencial de las especies nativas e introducidas de bambú en México.. 750095 records from Oiseaux de France métropolitaine en hiver 1977-1981. 4658 records from All herbarium specimens of grasses held at TAN herbarium. 548 records from Pollen counts of sediment core GeoB9503-5. 266 records from Chronicle of Nature - Phenology of Insects of Volzhsko-Kamsky National Nature Biosphere Rezerve. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_10-CTD121. 332 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 67 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 794 records from Macroarthropods, Narsarsuaq 2014, Greenland. 66620 records from Benthos monitoring in the intertidal mudflats of Pertuis-Charentais (Bay of Biscay) from 2004 on. 10774 records from Some Angiosperm Data of the Forest Herbarium Ibadan (FHI) Nigeria. 409 records from Records of fish species in coastal lagoons from Municipality of Arta, for the period 1999-2011. 24 records from Abundance of coccosphere-units of sediment core GIK23071-3. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-089. 272720 records from Parc_National_de_Port_Cros_2017_12_18. 15 records from Morphology and molecular data reveal the presence of two new species under Rhamdia quelen (Quoy & Gaimard, 1824) (Siluriformes: Heptapteridae) species complex. 85 records from Ecología de comunidades microbianas en las aguas subterráneas de Cuatrociénegas, Coahuila. 3 records from A new group of species within the bee genus Ruizantheda, with a revised key to the males of the genus (Hymenoptera: Halictidae: Caenohalictini). 20891 records from Brachycera (Diptera) records from Britain and Ireland to 1990. 438 records from Vermont Freshwater Mussel Atlas 1995. 3893 records from Colección Carcinológica de Yucatán. 15 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 145 (N.S) n° 38 (1), 2010 - Données faune. 4358 records from FrogWatch SA. 75 records from Données naturalistes de Françoise SERRE-COLLET. 374 records from (App 5) Relative contents of benthic foraminifera species in Holocene sediments from Core BP01-62/04. 2124 records from Range table from planktonic foraminifers in ODP Hole 144-872C. 1814 records from UKSBA Cyprus - Habitat Samples, 2019. 90 records from Swedish Malaise Trap Project (SMTP) - Pallopteridae. 11 records from ALP-PAGES_2017_12_18. 6936 records from Colección Herpetológica (Anfibios) del Museo de Historia Natural de la Universidad Industrial de Santander. 1994 records from Actualización de la base de datos de la Colección Regional Durango (Mammalia) (Tejido). 1 records from Museu Paraense Emílio Goeldi - Acanthocephala Collection. 22 records from Bachabschnitt der Nette (Osnabrück). 358 records from Species occurring in the mytilid and alvinellid communities within the 9°N hydrothermal field at the East Pacific Rise. 712 records from Programme ACT : Répartition Alouette des champs 2010 - 2014 Coordonnées GPS Lambert 93. 6 records from Ontogeny as an important part of integrative taxonomy in tergipedid aeolidaceans (Gastropoda: Nudibranchia) with a description of a new genus and species from the Barents Sea. 49 records from Ejemplares de Criptogamas de Chile en el Herbario CORD. 11232 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 8 records from Taxonomy of Litoria graminea (Anura: Hylidae), with descriptions of two closely related new species. 1 records from Dinoflagellate abundance of Hole 38-343. 6 records from A new species of the genus Liljeborgia Spence Bate, 1862 (Crustacea: Amphipoda: Liljeborgiidae) associated with the burrows of the spoon worm Urechis unicinctus in the Sea of Japan. 22 records from Description of lithologic section units of IODP Hole 325-M0054B. 332 records from Swedish Malaise Trap Project (SMTP) - Sepsidae. 2565 records from AlgaTerra. 820 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE272. 1144 records from MfN - Fossil vertebrates III. 47 records from Abundance and community structure of birds breeding in Kalahari woodland used as rangeland. 165 records from HSU Vertebrate Museum Mammals Collection. 13 records from Nannofossil abundance of Hole 9-80. 37445 records from ADDOMEx. 10 records from Umbyquyra gen. nov., a new tarantula spider genus from the Neotropical region (Araneae, Mygalomorphae, Theraphosidae), with a description of eight new species. 1 records from The InBIO Barcoding Initiative Database: Wesmaelius (Kimninsia) nervosus (Neuroptera, Hemerobiidae): a new species of brown lacewing for the Portuguese fauna. 124 records from (Table 2a) Downcore distribution of live benthic foraminifera of sediment core PS1394-1, Weddell Sea. 305 records from Foraminifera abundance of Hole 57-440B. 245 records from Informatisation des carnets de terrain de Georges Catherine. 16260 records from Acoustic monitoring data of avian species inside and outside the evacuation zone of the Fukushima Daiichi power plant accident. 26435 records from UTEP Insects (Arctos). 1 records from Revision of the Genus Schizoretepora (Bryozoa, Cheilostomatida) from the Atlantic-Mediterranean region. 10 records from Données naturalistes de DURON Cyril. 1339 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 39 records from Inventaire Faune. 31 records from New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico. 72 records from Registros de la araña del banano (Phoneutria boliviensis) en los departamentos de Antioquia, Huila y Tolima. 1 records from Revision of the genus Carybdea (Cnidaria: Cubozoa: Carybdeidae): clarifying the identity of its type species Carybdea marsupialis. 30 records from The larva of Amphigomphus somnuki Hämäläinen, 1996 and the first records of the genus Stylogomphus Fraser, 1922 for Thailand (Odonata: Gomphidae). 262 records from (Fig. 5) Distribution and stable isotope record of foraminifera, and ice-rafted debris of sediment core PS1230-1 (fig 5). 270 records from Planktic foraminifera abundance of Hole 42-375. 17827 records from Condition of rocky reef communities around Tasmania: fish surveys, Australia (1992-1995 and 2006-2007). 96 records from Planktic foraminifera abundance of Hole 32-305. 6 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-960A. 64 records from Anfibios y reptiles del páramo de Sumapaz - Proyecto Colombia Bio. 1514 records from Gemeinde Sursee. 2 records from Two new species of Hyalella (Crustacea, Amphipoda, Hyalellidae) from state of Rio Grande do Sul, Southern Brazil. 4 records from Sponges of the family Esperiopsidae (Demospongiae, Poecilosclerida) from Northwest Africa, with the descriptions of four new species. 183 records from Nannofossil abundance of Hole 67-496. 525 records from Relative abundance of benthic foraminifera in sediment core SO90-137KA. 852 records from Observatoire des Mammifères marins de l'Archipel Guadeloupéen. Suivi Dauphins Les Saintes. 569 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 841 records from Database on reference specimens for medicinal plants of the Rubiaceae family, conserved at the CNARP herbarium. 2 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 2 records from A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae). 525 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 361 records from Colección de Crustáceos del Instituto de Ciencias Naturales (ICN-MHN-Cr). 235 records from Pollen and spore abundance of Hole 42-381. 398 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Site 115-711. 1599 records from Inventaire des bois par espèce végétale de la forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 1563712 records from Biodiversitätsdatenbank des Landes Salzburg. 16 records from Nannofossil abundance of Hole 52-418. 84 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 11 records from Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae). 235 records from Chronicle of Nature - Phenology of Insects of Kaniv Nature Reserve. 3317 records from Estudio taxonómico y zoogeográfico de áreas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, México. 7 records from Swedish Malaise Trap Project (SMTP) - Mymar. 452 records from Nannofossil abundance of Hole 64-476. 7255 records from Colección general del plantas vasculares del Herbario JBB. 2375 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 45 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 1441 records from Cowan Tetrapod Collection - Herpetology. 147 records from Total foraminifera counts from multinet M31/3_MSN898. 186 records from Phytoplankton abundance at station CD46_0705C#4. 1 records from Eudorylaimus kahaqensis sp. n. (Nematoda: Dorylaimida: Qudsianematidae), an interesting new species from Iran. 13 records from Données additionnelles d'Echasse blanche Himantopus himantopus 1980-1991 nicheuse probable ou certaine (hors période atlas 1985-1989). 84 records from Shellfish (MNHM-MS). 29 records from Hemmerder Schelk (Unna). 2 records from The harvestman genus Taracus Simon 1879, and the new genus Oskoron (Opiliones: Ischyropsalidoidea: Taracidae). 30998 records from Elephant Seal Sightings, Macquarie Island. 5 records from New taxa and notes on crickets of the subfamily Landrevinae (Orthoptera: Gryllidae) from Brunei Darussalam, Borneo. 2 records from Annotated checklist of the false blister beetles (Coleoptera: Tenebrionoidea: Oedemeridae) from Iran. 3 records from Description of a new species of Music frogs (Anura, Ranidae, Nidirana) from Mt Dayao, southern China. 448 records from Hyperbenthos community in the salt marsh of Saeftinghe in 1990 and 1991. 16 records from jamaica_invasive_alien_species. 15 records from Integrative taxonomy reveals cryptic diversity in neotropical grasshoppers: taxonomy, phylogenetics, and evolution of the genus Sphenarium Charpentier, 1842 (Orthoptera: Pyrgomorphidae). 1 records from A new tardigrade species of the genus Neostygarctus Grimaldi de Zio et al., 1982 (Tardigrada, Arthrotardigrada) from the Great Meteor Seamount, Northeast Atlantic. 2 records from First record of Cephenniini on Christmas Island, with updated checklist of world Cephennomicrus species and summary of their distribution (Coleoptera, Staphylinidae, Scydmaeninae). 150 records from Schulgarten Huttenheim (Philippsburg/Baden). 1319 records from Inventaire et suivi Avifaune. 934 records from Botanic Garden of the Finnish Museum of Natural History. 89 records from Planktic foraminifera abundance of Hole 63-470A. 52 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2247-1. 7 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1024. 20 records from Búsqueda de poblaciones de la liebre endémica Lepus flavigularis. 697 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Wolf, (Canis lupus) Wild Boar (Sus scrofa) and Roe Deer (Capreolus capreolus) [camera-trapping] - [2011-2014]. 286 records from Inventory of the Heteroptera (Insecta: Hemiptera) in Komaba Campus of the University of Tokyo, a highly urbanized area in Japan. 14 records from New species of Australian microgastrine parasitoid wasps (Hymenoptera: Braconidae: Microgastrinae) documented through the ‘ Bush Blitz’ surveys of national reserves. 626 records from Estado actual de conservación de liebres y conejos en categoría de riesgo en México. 1249 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 80 records from Foraminifera distribution of sediment core SDSE189. 155 records from The ceratioid anglerfishes (Lophiiformes: Ceratioidei) of New Zealand. 2017 records from Flore des reliques forestières de la commune de Dangbo. 3 records from Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae). 74 records from Chronicle of Nature - Phenology of Mushrooms of Baikalsky State Nature Biosphere Reserve. 27 records from Planktic foraminifera abundance of Hole 18-174. 2693 records from California State University, Long Beach Mammals. 494 records from (Appendix 3) Abundances of benthic forminifera in DSDP Hole 74-525A. 234 records from Royal Saskatchewan Museum - Ichthyology Collection. 981 records from Monitoreo de la ocupación del Oso Andino Tremarctos ornatus en el Parque Nacional Natural Chingaza 2010. 2 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves Nidos (MFA-ZV-Or-N). 63 records from Données du/de la naturaliste Champagne Alain provenant de la base de donnée du SINP Île-de-France CETTIA. 2 records from Argia mauffrayi n. sp. from Ecuador (Odonata: Coenagrionidae). 200 records from Database_Dragonflies_ Madagascar Biodiversity Center PBZT. 133 records from Nematode abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 581 records from Butterflies_of_Singapore_and_Peninsular_Malaysia_(Pieridae). 2 records from Dinoflagellate abundance of Hole 71-513A. 182 records from Microzooplankton abundance measured on water bottle samples at station PS58/048-3. 201 records from Total foraminifera counts of multinet SO118_MSN1253. 3331 records from Digital Atlas of Trees and Wildlife in Thailand. 6288 records from Macroinvertebrate abundance data from the littoral zone of a number of large New Zealand lakes. 4 records from A new species of Pseudobunocephalus Friel, 2008 (Siluriformes: Aspredinidae) from the lower Tocantins and Mearim river drainages, North and Northeast of Brazil. 773 records from Foraminifera abundance of Hole 45-396. 4 records from A new species of Leptobrachella (Anura: Megophryidae) from southern Guangxi, China. 63 records from New contributions to the Eulophidae fauna from Morocco (Hymenoptera: Chalcidoidea) with comparison in the North African region. 382 records from Collection Echinodermata - ZMB. 260 records from Miljodir_naturtypekartlegging_2017. 244 records from WildesMoor bei Schwabstedt. 3914 records from EDP Foz-Tua: Macrophytes – Ecological Monitoring Program [2011-2015]. 434 records from Inventario herpetofaunístico del noroeste de Hidalgo. 379 records from Diatom abundance measured on water bottle samples at station PS58/046-3. 677 records from The Paleontological Collections at the Bayerische Staatssammlung für Paläontologie und Geologie. 3 records from A new subspecies of Glabroculus elvira (Eversmann, 1854) (Lepidoptera, Lycaenidae) from the Dzhungarian Gobi desert, Mongolia. 7 records from Description of lithologic section units of IODP Hole 325-M0052A. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR16. 212 records from Données des naturalistes POHIER et LEFORT provenant de la base de donnée du SINP Île-de-France CETTIA. 7920 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 10 records from More than just the number of denticles: morphometric and limb variability in Neotropical cladoceran Alonella dadayi (Crustacea: Cladocera: Chydoridae). 16388 records from CPAP - Herbário CPAP. 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 190 records from CNMA/Colección de Mamíferos de la Estación de Biología Chamela. 98 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 4 records from Taxonomic notes on Chinese Lamiini (Coleoptera: Cerambycidae: Lamiinae). 406 records from Harpactus Shuckard. 2968 records from Los crustáceos decápodos marinos: Actualización de la colección carcinológica de la Facultad de Ciencias Biológicas, UANL. 2189 records from Jardín Botánico Atlántico, Gijón: JBAG. 36 records from Microzooplankton abundance and biomass at station TT045_26-3. 51 records from Données du naturaliste MARCHAL Olivier provenant de la base de donnée du SINP Île-de-France CETTIA. 91 records from Données de la naturaliste Marie Melun. 1419 records from Diversity of algae in wetlands. 3647 records from Données rhopalocères collectées par le CEN Aquitaine entre 1970 et 2015. 2 records from A new species of freshwater crab of the genus Strengeriana Pretzmann, 1971, from El Jardín Natural Reserve, Quindío, Colombia (Crustacea: Decapoda: Pseudothelphusidae). 349 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 1 records from Integrative description of Macrobiotus canaricus sp. nov. with notes on M. recens (Eutardigrada: Macrobiotidae). 1137 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 72 records from Données sur les Opisthobranches et Planaires de Mayotte. 4 records from Microplankton counts and carbon biomass at station TT011_3-CTD33. 381 records from Estudio taxonómico de moluscos terrestres y dulceacuícolas de la región maya de México I. Reserva de la Biosfera Pantanos de Centla. 4 records from Open-holed trapdoor spiders of the genus Teyl (Mygalomorphae: Nemesiidae Anamini) from Western Australia’s Pilbara bioregion: a new species and expanded phylogenetic assessment. 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 129 records from Planktic foraminifera abundance of Hole 94-611. 3 records from Abundance of zooplankton in the Aral Sea. 11193 records from Baselines Initiative 16S rRNA gene dataset: Baselines Amplicon Release 1 (R1) Caribbean Sea near Curacao (including saline pond samples in Curacao) 2015. 2825 records from Distribution of dead benthic foraminifera in surface sediments of the Norwegian Sea (Table 3). 7 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 6 records from Two new species of the spider genus Wanniyala Huber & Benjamin, 2005 (Araneae Pholcidae) from Sri Lanka. 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 1389 records from Phytoplankton abundance in surface water during cruise CD61. 3 records from Discovery of a new species of Lacon Laporte (Coleoptera: Elateridae: Agrypninae) endemic to Cyprus, with a modified tarsal morphology. 29 records from Total foraminifera counts of trap L3_92_45. 88 records from "Schlechteberg" Ebersbach/Sa.. 8017 records from Colección de Herpetología del Instituto de Ciencias Naturales (ICN-MHN-Her). 24 records from 2019_nsmk_smpl_ms_20200603. 751 records from Programme ACT : Répartition Pie bavarde 2007 - 2011 Coordonnées GPS Lambert 93. 3 records from Two new species of amphipods (Crustacea: Amphipoda: Photidae) from Korean waters with a redescription of Gammaropsis longipropodi. 4484 records from (Table 1) Occurrence of selected planktonic foraminifers, other microfossils, and lithologic components at DSDP Hole 96-619. 2 records from Three new species of Synagelides Strand, 1906 from China (Araneae: Salticidae). 124922 records from DEEPEND: Microbiome and bacterioplankton rRNA gene sequence data collected from Gulf of Mexico seawater samples. Cruises DP03 and DP04 from Jan 2016 - December 2016. 119 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1371. 39 records from Nannofossil abundance of Hole 1-3. 1 records from A new species of Metatanais Shiino, 1952 (Crustacea, Tanaidacea, Paratanaoidea) from Australian coral reefs, with a redefinition of the genus. 641 records from Planktic foraminifera counts of sediment core V29-64. 8 records from Microzooplankton abundance and biomass at station TT054_7-18. 191 records from sediment microorganism Metagenome. 10 records from Occurrence of mammalia relicts at site Salzgitter-Lebenstedt. 696 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 1 records from A new Myxobolus (Cnidaria: Myxosporea) infecting the ornamental catfish Corydoras schwartzi from the Purus River in Brazil. 135 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - Birdrace-Pody&Co.-Plön. 807 records from Aquatic Insects from the Caatinga: checklists and diversity assessments of Ubajara (Ceará State) and Sete Cidades (Piauí State) National Parks, Northeastern Brazil. 4961 records from (Appendix II) Planktonic foraminiferal biostratigraphy of ODP Site 113-690. 2427 records from Base de datos y colección de distintos grupos del zooplancton de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano (Larvas de peces). 112 records from Oxygen isotopes, Mg/Ca ratios, sea surface temperature and counting of G. ruber morphotypes of sediment core MD01-2390. 1962 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Entomology National Collection (MACNEn). 2 records from A new deep-sea Cirripedia of the genus Heteralepas from the northeastern Atlantic. 237 records from Phytoplankton abundance during Arne Tiselius cruise AT91/2. 4203 records from SPC CoFish Fish Observations Federated States of Micronesia 2006. 1101 records from A species-level taxonomic review and host associations of Glyptapanteles (Hymenoptera, Braconidae, Microgastrinae) with an emphasis on 136 new reared species from Costa Rica and Ecuador. 403 records from Revision of Chondrocyclus s. l. (Mollusca: Cyclophoridae), with description of a new genus and twelve new species. 2 records from Two new species of Petrobunus from China (Opiliones: Laniatores: Petrobunidae). 55 records from SNH Invertebrate Site Condition Monitoring 2015: Rinns of Islay SSSI. 464 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 150 records from Registros de almeja (Polymesoda arctata) en la Ciénaga de pajarales. 18 records from "Biodiversidad en el valle de Cuatro Ciénegas". (Ácaros acuáticos). 17 records from Peces de la expedición en el páramo El Consuelo, Boyacá - Proyecto Boyacá BIO. 106 records from Phytoplankton abundance at station Rigel_3_2005-07 in July 2005, Chipana, Chile. 139730 records from Atlantic Reference Centre Museum of Canadian Atlantic Organisms - Invertebrates and Fishes Data. 229 records from Earthworms of mole burrows in the forest zone of Western Siberia. 3428 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 2 records from Lemyra persephone, a new autumnal species from Yunnan, southwestern China (Lepidoptera, Erebidae, Arctiinae). 724490 records from Finnish Floristic Database (Literature Sources). 180 records from (Table 7) Distribution of the large, many-chambered Globigerinelloides species in DSDP Hole 79-545. 4 records from Not endemic after all: Imparipecten Freeman, 1961 (Diptera: Chironomidae) described from the Neotropical Region. 536 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 72176 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 1763 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 32301 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 529 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 4534 records from Amphibian specimens. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 230 records from Inventaire avifaune. 2 records from A new Paramathes Boursin, 1954 (Lepidoptera, Noctuidae) species from China. 20871119 records from iNaturalist Research-grade Observations. 37 records from Content of coarse fraction and G. menardii in sediment corev V16-202. 143 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 277 records from Aunar esfuerzos y recursos técnicos, económicos y humanos con el fin de adelantar acciones de investigación para estimar las poblaciones y monitorear en el tiempo la rana venenosa Oophaga lehmanni en la localidad La Cascada (Valle del Cauca). 1 records from Capalictus, a new subgenus of Lasioglossum Curtis, 1833 from South Africa, with description of three new species (Hymenoptera, Apoidea, Halictidae). 1 records from A synopsis of the genus Dorcasta Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Apomecynini). 117 records from Nannofossil abundance of Hole 41-366A. 100 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 24 records from Abundance of benthos infauna at station PS1240-1. 1 records from Dolichocephala Macquart of Thailand (Diptera: Empididae: Clinocerinae). 124721 records from CAS Botany (BOT). 1 records from A new genus of Oxypodina from Kyrgyzstan (Coleoptera, Staphylinidae, Aleocharinae, Oxypodini). 61 records from Plasm bearing foraminifera counts from M35/1_MSN1059. 1305 records from (Table 3) Distribution of benthic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 508 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Zooplankton sampling on board the Norwegian R/V Jan Mayen, program ALV. 129 records from Range table from benthic foraminifers in ODP Hole 198-1207B. 178 records from (Fig. 3) Relative abundance of Neogloboquadrina pachyderma (s) in sediment core MD99-2343. 830 records from Soil DNA extracted from Robinson Ridge, East Antarctica Raw sequence reads. 598 records from MBON POLE TO POLE: SANDY BEACH BIODIVERSITY OF YUCATAN COAST. 3 records from New species of Prolachesilla Mockford & Sullivan (Psocodea: ‘ Psocoptera’: Lachesillidae: Graphocaeciliini) from Bolivia and Mexico. 43403 records from Tartu University fossil collections. 4 records from Two new species of Nealiolus Mason (Hymenoptera, Braconidae, Brachistinae) reared from pest weevils (Coleoptera, Curculionidae). 2 records from Description of a new subspecies of Prosopocoilus antilopus (Swederus, 1787) (Coleoptera: Lucanidae) from Annobón Island, Gulf of Guinea. 22 records from Fifteen new species and a new country record of Labomimus Sharp from China, with a checklist of world species (Coleoptera: Staphylinidae: Pselaphinae). 2 records from First record of the genus Phanoperla Banks, 1938 (Plecoptera: Perlidae) from mainland China, with description of a new species. 3756 records from UMNH Reptiles and Amphibians Collection (Arctos). 490 records from Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 165 records from Mortensen Th. And Steuer Ad. 1937. The fishery grounds near Alexandria. XIII Echinoderma. Notes and Memoirs No 21. Hydrobiology and Fisheries Directorate, Egypt. 54534 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 114 records from BIRDRACE Di-Bi-Di-Birder. 441 records from Range table from planktonic foraminifers in ODP Hole 155-930C. 1957 records from BioGIS - Marine snails - HUJ collections. 111 records from Ökologischer Weinberg (Guntersblum). 611 records from Données du Râle gris sur le territoire de la Guadeloupe. 8 records from Five new species of the Acantholycosa - complex (Araneae: Lycosidae) from Mongolia. 5 records from Review of the Nassarius pauperus (Gould, 1850) complex (Nassariidae): Part 3, reinstatement of the genus Reticunassa, with the description of six new species. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 2203 records from Molluscus specimens of Toyohashi Museum of Natural History. 33 records from Four new Amynthas and Metaphire earthworm species from nine provinces in southern China. 50902 records from Anfibios y reptiles de las regiones 30 (Parque Natural Sierra Maderas del Carmen); 31 (Sierra El Burro-Río San Rodrigo); 36 (Sierra La Encantada); y 37 (Sierra El Pino), Coahuila. 9 records from A new species and the phylogeny of the South American genus Gromphas Brullé, 1837 (Coleoptera: Scarabaeidae: Scarabaeinae: Phanaeini). 688 records from données arachnologiques de CARR David. 19 records from Fishes from the Auckland and Campbell Islands, Cape Expedition, 1942-1944. 40 records from Two new species of Ecpatia Turner, 1902, and the first records of Ecpatia sciachroa Hampson, 1926 and Ecpatia obscura Holloway, 2009 from Thailand (Lepidoptera: Noctuidae, Noctuinae). 48 records from Ruhrwiesen bei Neheim-Hüsten. 293 records from Macrofauna, entomofauna y vegetación vascular de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 4 records from Nannofossil abundance of Hole 3-22. 2 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 102 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-14. 270 records from ABC Matandwe Forest Reserve Vegetation Survey. 50049 records from Fungi of Costa Rica (INBio). 69797 records from Intermountain Herbarium (Vascular plants & algae). 1170 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 48 records from Planktic foraminifera abundance of Hole 25-241. 1873 records from Microbial community structure of chronically polluted marine sediments from a cold region of the southern hemisphere. 91356 records from 臺灣兩棲類資源調查與教育宣導推廣計畫 Resources survey and education advocacy to promote for Taiwan amphibian resources. 1381 records from (Appendix B) Nannofossil abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 134 records from BIRDRACE Griffin Wood Warblers. 184 records from Kystfuruskoger 2015. 156 records from Deep-Sea holothurians (Echinodermata, Holothuroidea) of the Colombian Southern Caribbean Sea. 1 records from On a new marine podocopid genus and species (Ostracoda: Hemicytheridae) from Brazil. 1 records from Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 2 records from Microzooplankton abundance and biomass at station TT054_24-22. 3 records from A new species of freshwater crab of the genus Himalayapotamon Pretzmann, 1966 (Decapoda, Brachyura: Potamidae: Potaminae) from Uttarakhand, northern India. 112 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 2143 records from Range table from benthic foraminifers in ODP Hole 154-929A. 1 records from New articulated asteroids (Echinodermata, Asteroidea) and ophiuroids (Echinodermata, Ophiuroidea) from the Late Jurassic (Volgian / Tithonian) of central Spitsbergen. 15 records from Sphyraena stellata, anew barracudafromthe Indo-Pacific, with redescriptionsofS. helleri Jenkins, 1901 and S. novaehollandiae Günther, 1860 (Perciformes: Sphyraenidae). 2 records from A new pea crab species of the genus Arcotheres Manning, 1993 (Crustacea: Decapoda: Brachyura: Pinnotheridae) from India. 670 records from Project for Reef Fish Monitoring. 5205 records from FBIP:IZIKO-UCT:Historical Survey (1930-1980). 76 records from An update on the spider genus Hexophthalma (Araneae: Sicariidae) in the Afrotropical region, with descriptions of new species. 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 4124 records from Inventaire de la flore des ENS des Pyrénées-Atlantiques 2011-2012. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 26270 records from JCT AVH data. 35 records from Macrohongos en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 88634 records from Hymenoptera collection of the Finnish Museum of Natural History. 912 records from JOIw - Xiloteca Joinvillea. 41 records from Planktic foraminifera counts of sediment core V28-128. 4 records from Olbiogaster Osten Sacken (Diptera: Anisopodidae) from Mexico, with the description of three new species. 70 records from Incidence of pests and viral disease on pepino (Solanum muricatum Ait.) in Kanagawa Prefecture, Japan. 16 records from (Table 4b) Abundances of Globorotalia menardii in sediment core INMD-113BX. 4 records from Black grouse lek survey in Wester Ross and Skye 2009. 490 records from Sequences obtained from two sponge genera (Hyrtios, Aiolochroia), one zoanthid (Palythoa), and marine sediments. Metagenome. 155 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 179 records from The female velvet ants (aka modkhong) of southern Thailand (Hymenoptera: Mutillidae), with a key to the genera of southeast Asia. 120 records from Flora polínica de las llanuras de Sonora, al sur de Hermosillo. 555 records from Planktic foraminifera abundance of Hole 49-407. 54 records from VFD-H: MIttelgebirgsweide. 339 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE218. 88 records from Microzooplankton abundance measured on water bottle samples at station PS65/587-1. 134 records from Nannofossil abundance of Hole 7-62A. 3224 records from Amphibiens de Guyane. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 9 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 11 records from Nannofossil abundance of Hole 9-82. 575 records from Nannofossil abundance of Hole 75-530A. 24 records from Planktic foraminifera abundance of Hole 20-200A. 2 records from Two new species, including one representing a new genus, of the West African millipede family Campodesmidae (Diplopoda: Polydesmida). 4356 records from (Table 18) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-593. 50 records from Smear slide analysis on sediment core GeoB4206-1. 5 records from Collection Myriapoda - SNSD. 49540 records from Dreal Corse - Base Ogreva. 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 78605 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 1380 records from (Table 9) Benthic foraminifera in early-middle Miocene sediments of DSDP Hole 90-591B. 714 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 25 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 12 records from Sarcodine counts and carbon biomass at station TT011_10-CTD123. 3546 records from Dorset SW Pilot species dataset. 66 records from Rhopalocera of Martinique. 9 records from Benthic macrofauna abundance of sediment core 13077-087. 1914 records from Herbario de Hongos de la Universidad de Salamanca: SALA-Fungi. 394 records from Étude de lépidoptérologie comparée. 48769 records from Flora of the Stołowe Mts.. 3 records from A redescription and a synonym in the South Asian millipede genus Xenobolus Carl, 1919 (Spirobolida, Pachybolidae).
Keywords: GBIF; biodiversity; species occurrences